The Perceptions of Student Teachers of Online Pedagogical Courses and Assessment Practices in Finnish Subject Teacher Education - Toni Mäkipää; Raili Hildén; Tanja Samulin (MDPI AG, 2022)
The purpose of this case study was to explore how student teachers at the University of Helsinki perceived pedagogical courses in emergency remote teaching. The dataset consists of the responses of 79 students to an online questionnaire and interviews with five students. Descriptive statistics, multiple linear regression analysis, and content analysis were used to analyze the data. The students pointed out that, on average, teachers have mastered the pedagogy of remote teaching well, although older teachers had more challenges than younger teachers. The quality of teaching was reported as being high. Teachers' pedagogical knowledge was the strongest predictor of successful remote teaching. In terms of assessment, teachers mostly used essays and other written assignments to assess students' achievement. According to most students, the assessment practices were implemented successfully. The results provide insights for developing remote teaching in teacher education.